First record of cydnidae (Hemiptera: Heteroptera) from easter island, chile Primer registro de la familia cydnidae (Hemiptera: heteroptera) en isla de pascua, chile - Vargas, Catalina J.; Faúndez, Eduardo I.; Carvajal, Mariom A. (My University, 2021)
A new record from insular Chile for the Neotropical and Andean cydnid Melanaethus spinolae (Signoret, 1864) is presented. Specifically, the new record comes from Easter Island, making M. spinolae the first burrower bug found in this Oceanic island. The possible causes of the range expansion of this taxon are commented.
Keywords: cydninae; faunistics; pentatomoidea